2018
DOI: 10.1039/c8ra04878a
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of immobilization conditions of cellulosic lyotropic liquid crystals in monomeric solvents by in situ polymerization and achievement of dual mechanochromism at room temperature

Abstract: We obtained cellulosic/synthetic polymer composites incorporating a cholesteric liquid crystalline structure by in situ polymerization and accomplished dual mechanochromism at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Once a cholesteric liquid crystalline phase has developed, the spacing between each plane of the helicoidal arrangement is dependent on the fraction of polymer in the mesophase. Generally, a higher concentration leads to a smaller pitch and a blue-shift of the reflection spectrum of the chains as more closely packed. ,,,,, ,,,,,,,, Specifically, a power law dependence between the pitch p (units of μm) and concentration ϕ p (units of wt %) is repeatedly reported like in eq . ,, …”
Section: Cholesteric Solutions Of Cellulose Derivativesmentioning
confidence: 93%
“…Once a cholesteric liquid crystalline phase has developed, the spacing between each plane of the helicoidal arrangement is dependent on the fraction of polymer in the mesophase. Generally, a higher concentration leads to a smaller pitch and a blue-shift of the reflection spectrum of the chains as more closely packed. ,,,,, ,,,,,,,, Specifically, a power law dependence between the pitch p (units of μm) and concentration ϕ p (units of wt %) is repeatedly reported like in eq . ,, …”
Section: Cholesteric Solutions Of Cellulose Derivativesmentioning
confidence: 93%
“…In prior work EC/PAA films expressed SICDI only above 130 • C because of the T g of the films. Thus Miyagi and Teramoto [57][58][59] also expanded the conditions where such films can manifest SICDI. Accordingly, they prepared propionylated HPC (PHPC; Figure 2k), which has a low T g (ca.…”
Section: Mechanochromic Filmsmentioning
confidence: 96%
“…Fukawa et al [60] reported a similar phenomenon. Spin-lattice relaxation analyses of PHPC/synthetic polymer ChLC films by solid-state nuclear magnetic resonance spectroscopy indicated that the immobilization efficiency was high for the films where PHPC and synthetic polymers were not completely compatible [57,58]. This can be attributed to the way that the complete mixing of cellulose derivatives and synthetic polymers disturbs the interaction of mesogenic cellulosic chains.…”
Section: Mechanochromic Filmsmentioning
confidence: 99%
“…In our previous studies, we prepared cellulosic/polymer ChLC composite films by in situ polymerization of the corresponding cellulosic/monomer lyotropic ChLC. The obtained ChLC composites showed not only color change but also CD inversion by applying compressive stress. Furthermore, the compressed films recovered their original CD by thermal treatment. As far as we know, there have been no other reports that specifically focus on stress-induced dynamic CD inversion of solid ChLC materials.…”
Section: Introductionmentioning
confidence: 95%